2021
DOI: 10.3389/fpubh.2021.670485
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Science, Perceived Media Exaggeration About COVID-19, and Social Distancing Behavior

Abstract: For many individuals, the media function as a primary source of information about preventative measures to combat COVID-19. However, a considerable number of citizens believe that the media coverage about pandemics is exaggerated. Although the perception of media exaggeration may be highly consequential for individual health behaviors, we lack research on the drivers and consequences of this perception. In a two-wave panel study, we examined associations between trust in science, perceptions of media exaggerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
1
9
0
2
Order By: Relevance
“…This study contributes to the limited scientific literature regarding the association between COVID-19 preventative behaviors, the trustworthiness of information, and sources of information. Our findings are comparable to earlier studies that found that people who had higher trust in government COVID-19 messaging were more likely to adopt preventive behaviors [ 7 , 10 - 12 , 14 , 15 ]. In alignment with existing work, our respondents felt that preventive measures, such as social distancing, would help prevent the disease spread, but only a minority of people strongly agreed that social distancing was easy to do [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study contributes to the limited scientific literature regarding the association between COVID-19 preventative behaviors, the trustworthiness of information, and sources of information. Our findings are comparable to earlier studies that found that people who had higher trust in government COVID-19 messaging were more likely to adopt preventive behaviors [ 7 , 10 - 12 , 14 , 15 ]. In alignment with existing work, our respondents felt that preventive measures, such as social distancing, would help prevent the disease spread, but only a minority of people strongly agreed that social distancing was easy to do [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the source of information and the trustworthiness of the information is potentially critical. Earlier studies conducted in multiple settings have found that trust in COVID-19 health information from government officials and public health agencies (PHAs) was related to an increase in people's perceived level of risk, greater severity of the disease if infected, and greater belief in the effectiveness of preventive behaviors [10][11][12][13][14][15][16][17]. Political ideologies, religiosity, and conspiracy ideation have been identified to play a substantial role mediating trust in COVID-19 information and guidelines [13,15], highlighting the demographic differences influencing trust in health information and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Angefangen mit Putnams (1993) Ausführungen zu fehlendem Vertrauen und der Erosion der amerikanischen Demokratie, findet die Variable immer wieder Eingang in verschiedene politikwissenschaftliche Untersuchungen. Im Zuge der Pandemie durch den rally-effect (Bol et (Neureiter et al 2021). Es kann davon ausgegangen werden, dass die Demokratiezufriedenheit in der Pandemie auch durch die Krisenberichterstattung beeinflusst wird.…”
Section: Drittvariablenunclassified
“…Research suggests that vaccine efforts might need to go beyond communication campaigns correcting misinformation about COVID-19 vaccines and should focus on re-establishing public trust in government agencies [ 33 ]. Trust in science may positively affect individuals’ social distancing behavior by decreasing perceived media exaggeration about COVID-19 [ 34 ]. Trust is a critical factor that encourages people to comply with public health regulations.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%